You Can Only Die Thrice: Death and Dying of a Human Body in Psychoanalytical Perspective - Šterk, Karmen (Journal of religion and health, 2010)
This paper compares the (cultural) necessity of death/dying, perceived as a sequence of ImaginaryRealSymbolic, to Van Gennep's three-staged rite of passage. If this logic is disrupted, the subject responsible necessitates attribution of special social status and can come to embody the imagery of a life worth living. This philosophical framework, which includes epistemologies borrowed from medical anthropology, demonstrates there is more for humans to lose than biological (Real) life; a far greater loss is to exist without (Symbolic) reason to live. A critique of prevalent quantitative methodology in assessing links between spirituality and the human body is added.